MoS2/WSe2 nanohybrids for flexible paper-based photodetectors. (12th May 2021) - Pataniya, Pratik M; Patel, Vikas; Sumesh, C K
Abstract: Flexible photodetectors functionalized by transition metal dichalcogenides have attracted great attention due to their excellent photo-harvesting efficiency. However, the field of optoelectronics still requires advancement in the production of large-area, broad band and flexible photodetectors. Here we report a flexible, stable, broad band and fast photodetector based on a MoS2 /WSe2 heterostructure on ordinary photocopy paper with pencil-drawn graphite electrodes. Ultrathin MoS2 /WSe2 nanohybrids have been synthesized by an ultrahigh yield liquid-phase exfoliation technique. The thin sheets of WSe2, and MoS2 contain two to four layers with a highly c-oriented crystalline structure. Subsequently, the photodetector was exploited under ultra-broad spectral range from 400 to 780 nm. The photodetector exhibits excellent figure of merit such as on/off ratio of the order of 10 3, photoresponsivity of 124 mA W −1 and external quantum efficiency of 23.1%. Encouragingly, rise/decay time of about 0.1/0.3 s was realized, which is better than in previous reports on paper-based devices.